REGIONAL TOURISM OPPORTUNITIES AND SAFETY CONCERNS - Umirova Dilnoza Safarovna (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is aimed at developing the regional tourism potential and improving the impact of the pandemic on tourism, there is also information about the rich historical and cultural monuments, nature and other tourist resources of Uzbekistan. The role of world tourism in the economy is discussed. In addition, information on general accommodation facilities in the territory of Uzbekistan was studied and analyzed. Suggestions and recommendations have been developed to increase the regional tourism potential.